A framework of challenges of the transition from E-Government to M-Government in the United Arab Emirates - Alharmoodi, Badir Yousif Ahmed Rafee (Tanjong Malim, 2023)
A framework of challenges of the transition from E-Government to M-Government in the United Arab Emirates by Alharmoodi, Badir Yousif Ahmed Rafee